2005
DOI: 10.1103/physrevlett.94.226102
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Step Bunching Instability during Surface Growth

Abstract: We study the step bunching kinetic instability in a growing crystal surface characterized by anisotropic diffusion. The instability is due to the interplay between the elastic interactions and the alternation of step parameters. This instability is predicted to occur on a vicinal semiconductor surface Si(001) or Ge(001) during epitaxial growth. The maximal growth rate of the step bunching increases like F 4 , where F is the deposition flux. Our results are complemented with numerical simulations which reveals … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 23 publications
4
37
0
Order By: Relevance
“…The results of theoretical study [9] agree with the experiments [7,8]. However, the step motion in sublimation at the low temperature has not been observed.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The results of theoretical study [9] agree with the experiments [7,8]. However, the step motion in sublimation at the low temperature has not been observed.…”
Section: Discussionsupporting
confidence: 84%
“…Frisch and co-workers [9] theoretically studied the step bunching by one-dimensional step flow model. They showed that the alternation of the surface diffusion is not important for the bunching.…”
Section: Introductionmentioning
confidence: 99%
“…When the difference in terrace width is small [20], δV is proportional to F 2 . In the present case, the tight step pairs are formed and the difference in terrace width is large.…”
Section: Instabilities With Impermeable Stepsmentioning
confidence: 99%
“…Frisch and co-worker [20] theoretically studied the step bunching. They used a step flow model, in which the anisotropy of the surface diffusion and the kinetic coefficients are changed alternately, and showed that the alternation of the kinetic coefficients causes the step bunching on the growing vicinal face.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation